Conditor urbium. Trajans Urbanisierungspolitik in den Donauprovinzen - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2018)
The victory in the war with Dacians set off a number of major administrative and administrative reforms conducted by Trajan in the Danubian provinces. Some of the vital elements of the reforms included veteran settlement and establishment of numerous towns – coloniae and municipia. As many as eighteen were thus established in the region during Trajan’s reign.